Multimodal-Based Mobile Application : A Development of Prototype for Accessing Students' Academic Results at UUM - Lim, Chee Chian (2004)
The aim of project is to develop a prototype of multimodal-based mobile application for retrieving student's results at UUM. The paper describes the system design and development process by using various software and design guidelines. This system accepts input both in spoken and stylus and provides feedback in graphics and text. User can choose at anytime which of the input modalities he/she prefers to use. A usability testing was carried out in which six subjects were asked to evaluate the prototype. This project has found that usability rates are rather high and respondents are well-accepted this prototype This project an be served as a model for future studies in developing multimodal-based mobile application.